Tidal stream energy resource assessment of the Anglesey Skerries - Serhadlioǧlu, S; Adcock, T; Houlsby, G; Draper, S; Borthwick, A (2013)
Many candidate sites for tidal stream power devices can be classified as headlands. This paper analyses one such site, off Anglesey. In order to investigate the disturbance to the local flow field due to the operation of tidal arrays and evaluate the extractable power at the site, a two-dimensional depth-averaged shallow water model of the naturally occurring tidal dynamics of the south-west UK and Irish Sea has been developed and validated. In the model, the effect of tidal arrays is represented by line discontinuities where upstream and downstream heads are related by Linear Momentum Actuator Disk Theory. A parametric study to investigate the importance of array locations, the connectivity of the arrays and local blockage effects on the available power has been undertaken. General conclusions from this analysis are that it is usually advantageous to arrange tidal turbines in long rows rather than as a number of rows in series, and that arrays with higher local blockage outperform arrays with lower blockage. © 2013 Elsevier Ltd. All rights reserved.